Factors Associated with Self and Informant Ratings of the Quality of Life of People with Dementia Living in Care Facilities: A Cross Sectional Study - Beer, C.; Flicker, L.; Horner, Barbara; Bretland, N.; Scherer, S.; Lautenschlager, N.; Schaper, F.; Almeida, O. (Public Library of Science (PLoS), 2010)
Background: There is no consensus regarding the optimal approach to assessment of the quality of life of people with dementia. We undertook the present study to describe and determine the factors associated with ratings of the quality of life of a cohort of people with dementia living in a residential care facility. Methodology/Principal Findings: 351 people with dementia living in residential care facilities, and their staff and family informants participated in this cross sectional observational study. Quality of life was measured using self (Quality of Life in Alzheimer’s Disease [QoL-AD] scale), and informant (QoL-AD and Alzheimer’s Disease Related QoL Scale) reports. 226 people (64%) with dementia (median MMSE 17; 12–21) were able to self rate the QoL-AD scale and these subjects’ ratings were compared to ratings by staff and family. Both staff and family informant ratings of the QoL-AD underestimated self ratings (mean difference 27.8, 95% CI 28.8, 26.7 for staff rated QoL-AD; and mean difference 27.2, 95% CI 28.5, 26.0 for family rated QoL-AD). Self ratings of QoL were lower among people who were restrained, had fallen or had pain. Informant ratings of the QoL of the participants with dementia were consistently and significantly lower for people with severe cognitiveimpairment, who had fallen, had presence of neuropsychiatric symptoms, or where care giver distress was present.Documented restraint, reported pain and neuropsychiatric symptoms were independently associated with lower self rating of the QoL-AD in multivariate models. Cognitive impairment, case conferencing, hospitalizations and neuropsychiatric symptoms were found to be independently associated with staff rated ADRQL. Conclusions: The majority of people with dementia living in residential care facilities can rate their own QoL. Informant ratings underestimate self ratings of QoL of people with dementia, and appear to be associated with factors which are notassociated with self ratings.